Efektivitas Metode Tasmi’ Terhadap Kelancaran Hafalan Al-Qur’an Santri Puteri Asrama Al-Husna Pondok Pesantren Darul Ulum Jombang - Abdul Rouf; Eny Fatimatuszuhro Pahlawati; Kholiqul Firnanda (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
ABSTRACT This quantitative study aimed to determine the effectiveness of the Tasmi' method on the fluency of Quran memorization among female students at the Al-Husna Dormitory at the Darul Ulum Islamic Boarding School in Jombang. Data collection methods included observation, interviews, questionnaires, and documentation. The data were analyzed statistically using the product-moment correlation formula. The results of this study indicate that, based on the product-moment correlation analysis, the Tasmi' method correlates significantly with the fluency of Quran memorization among female students at the Al-Husna Dormitory, with a correlation index (rxy) of 0.59. These results can be interpreted as 0.4438 at the 5% significance level and 0.5614 at the 1% significance level. Therefore, since rxy is greater than the significance level, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So there is a positive influence of the effectiveness of the Tasmi' method on the fluency of memorizing the Al-Qur'an of female students at the Al-Husna Dormitory of the Darul Ulum Islamic Boarding School, Jombang. Keywords: Tasmi' method, Al-Qur'an memorization, female students